Atom interferometry : proceedings of the International School of Physics "Enrico Fermi", course 188, Varenna on Lake Como, Villa Monastero, 15-20 July 2013 - Tino, G. M.; Kasevich, M. A. (International School of Physics 'Enrico Fermi', 2014)
Since atom interferometers were first realized about 20 years ago, atom interferometry has had many applications in basic and applied science, and has been used to measure gravity acceleration, rotations and fundamental physical quantities with unprecedented precision. Future applications range from tests of general relativity to the development of next-generation inertial navigation systems. This book presents the lectures and notes from the Enrico Fermi school ""Atom Interferometry"", held in Varenna, Italy, in July 2013. The aim of the school was to cover basic experimental and theoretical